Faktor Yang Mendorong Remaja Dalam Menggunakan Aplikasi Tiktok - Devy Putri Kussanti (Universitas Bina Sarana Informatika, 2020)
With the presence of technological advances and communication today is also accompanied by the many social media circulating in the community. One of them is Tiktok, which originated from China and is now widely used in Indonesia. By capitalizing on the concept of entertainment that is easily applied by the community, especially children and adolescents, Tiktok is increasingly becoming the prima donna in the world of social media. From various walks of life people are certainly familiar with and have participated in Tiktok content. The convenience provided by the application maker is evident from the existence of instructions that are young in the use of Tiktok. Even teenagers aged 13-15 years have now made Tiktok a consumption of social media every day. Analysis of the data used by the authors in this study aims to answer the questions listed in the identification of problems. This study uses descriptive quantitative analysis techniques with a questionnaire method. Then in the application in population calculations and samples consisting of several teenagers aged 13-15 years who are in the vicinity of housing, with the level of early junior high school education regarding the factor of the use of Tiktok.